Modern methods of tomographic studies in diagnosing internal damages of the knee joint - Vyrva, Oleg; Levitskaya, Liliya; Yeroshenko, Igor; Bocharov, Igor; Shevchenko, Igor; Putria, Igor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
Statistic data of internal damages in the knee joint are presented on the basis of an analysis of results of spiral computed arthrography with contrast saturation (118 patients) and magnetic resonance tomography (158 patients). In particular, it was revealed that meniscus damages were the most common ones (79.3 %). It is proved that the above techniques can be recommended as reliable low-invasive diagnostic procedures in damages of the knee joint along with supersonic and arthroscopic examinations. Examples of the commonest kinds of damages with this localization are described.